Divide-by-Three Injection-Locked Frequency Dividers with Direct Forcing Signal - Antonio Buonomo; Alessandro Lo Schiavo (Journal of Electrical and Computer Engineering)
Divide-by-three frequency dividers with direct forcing signal are analyzed, and the actual locking mechanism underlying their operation is highlighted. In particular, it is shown that the locking mechanism cannot be explained with the mixing between signals, as commonly made in the literature. An analytical procedure based on the averaging method is developed for solving the equation describing such dividers, and the first approximation to the oscillation in the locked states is predicted. The amplitude and phase of the output voltage in steady state as well as the locking range are derived in terms of the circuit parameters, obtaining useful design guidelines. The derived results are shown to be very close to SPICE simulations for a 0.13 um RF-CMOS process.